Deletion phenomena in comparative constructions English comparatives in a cross-linguistic perspective - Bacskai-Atkari, Julia (Open Generative Syntax, 2018)
This book provides a new analysis for the syntax of comparatives, focusing on various deletion phenomena affecting the subclause. In particular, the proposed account shows that Comparative Deletion is merely a surface phenomenon that can be drawn back to the overtness of the comparative operator and the availability of lower copies of a movement chain, and it is thus subject to both language-internal and cross-linguistic variation. The main focus of the book is on English, yet other languages are also discussed for comparative purposes, with the aim of showing what the idiosyncratic properties of English comparatives are.